Pengaruh Stres Kerja dan Konflik Kerja Terhadap Kinerja Kurir Pada PT Garuda Express Nusantara (J&T Express) Kota Pekanbaru - Arestina Delima Rajagukguk; Dodi Agusra; Kiki Joesyiana (Pelantar Press, 2024)
The purpose of this research was to determine the influence of work stress and work conflict on employee performance at PT. Garuda Express Nusantara Pekanbaru City. This research was conducted on December 2021 until June 2022 at PT Garuda Express Nusantara (J and T Express) Pekanbaru City located at Harapan Raya Street Pekanbaru City, Riau Province. The target of this research was the employee working at PT Garuda Express Nusantara Pekanbaru City. The research population were 91 employees. The samples selected were 91 employees obtained from Saturated Sampling Technique where all populations are made as samples. The data were gained through questionnaire distribution. The analysis method used was multiple linear regression analysis by using Statistics Product Service and Solution (SPSS) Program Version 20.0. Based on the hypothesis and research result, it could be concluded that work stress and work conflict have significant influence on sprinter employee performance at PT Garuda Express Nusantara Pekanbaru City which means that the higher work stress and work conflict then the lower employee performance and likewise. Work stress and work performance gave contribution 43.3% on employee performance while the rest 56,7% were influenced by other factors..